Enhanced expression of retinoic acid receptor alpha (RARA) induces epithelial‐to‐mesenchymal transition and disruption of mammary acinar structures. Issue 2 (22nd September 2014) - Doi, Ayano; Ishikawa, Kosuke; Shibata, Nao; Ito, Emi; Fujimoto, Jiro; Yamamoto, Mizuki; Shiga, Hatsuki; Mochizuki, Hiromi; Kawamura, Yoshifumi; Goshima, Naoki; Semba, Kentaro; Watanabe, Shinya
Abstract: The early steps of mammary tumorigenesis include loss of epithelial cell polarity, escape from anoikis, and acquisition of proliferative capacity. The genes responsible for these processes are predicted to be early diagnostic markers or new therapeutic targets. Here we tested 51 genes coamplified with ERBB2 in the 17q12–21 amplicon for these tumorigenic activities using an MCF10A 3D culture‐based screening system. We found that overexpression of retinoic acid receptor α (RARA) disrupted normal acinar structure and induced epithelial‐to‐mesenchymal transition (EMT). The mRNA levels of known EMT‐inducing factors, including SLUG, FOXC2, ZEB1, and ZEB2, were significantly increased upon RARA overexpression. Knockdown of ZEB1 suppressed the RARA‐mediated EMT phenotype. These results suggest that overexpression of RARA enhances malignant transformation during mammary tumorigenesis. Highlights: Retinoic acid receptor alpha (RARA) was identified as a transforming gene. Enhanced expression of RARA triggered collapse of mammary luminal structures. RARA overexpression induced epithelial‐to‐mesenchymal transition (EMT). Knockdown of ZEB1 suppressed RARα‐induced EMT phenotypes.